2017
DOI: 10.1177/1866802x1700900103
|View full text |Cite
|
Sign up to set email alerts
|

The Old Rules No Longer Apply: Explaining Narco-Assassinations of Mexican Politicians

Abstract: Between 2005 and 2015, organized criminal groups murdered 209 politicians in Mexico. This paper explains why. It argues that the two interwoven trends of political and criminal pluralization in Mexico fostered the conditions for a new type of criminal violence against politicians. Mexican politicians are now targeted for accepting illicit money as well as for standing up to criminals. Moreover, this violence is evidence of an alarming and persistent pattern in Mexico of politicians enlisting criminal organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…In contrast, we expect PRI incumbents to be more willing to sustain informal protection deals created under the one-party rule (Ríos, 2015;Blume, 2017;Trejo and Ley, 2017;Shirk and Wallman, 2015). In these places, we expect that collusive agreements between DTOs and governors, local prosecutors, and police are more likely to persist, translate into higher levels of impunity, and, in turn, produce higher levels of DTO extortion.…”
Section: Dto Relationships With the Statementioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, we expect PRI incumbents to be more willing to sustain informal protection deals created under the one-party rule (Ríos, 2015;Blume, 2017;Trejo and Ley, 2017;Shirk and Wallman, 2015). In these places, we expect that collusive agreements between DTOs and governors, local prosecutors, and police are more likely to persist, translate into higher levels of impunity, and, in turn, produce higher levels of DTO extortion.…”
Section: Dto Relationships With the Statementioning
confidence: 94%
“…On the other hand, the PRD lacked the federal resources provided to PAN states, which made them significantly weaker. Existing literature has shown that PRD governments have been disproportionately targeted by DTOs for assassination (Trejo and Ley, 2016;Blume, 2017). Politicians get killed for a variety of reasons, including (1) accepting money from a criminal group and then getting caught in fighting between DTOs;…”
Section: Dto Relationships With the Statementioning
confidence: 99%
See 1 more Smart Citation
“…As Chacón (2018) shows, armed groups in Colombia have used targeted violence to capture fiscal transfers from national governments to municipalities in order to finance war. Blume (2017) and Trejo and Ley (forthcoming) show that drug cartels in Mexico more commonly attack local authorities and seek to capture local governments where turf wars are more intense. Trejo and Ley (forthcoming) also show that drug cartels and OCGs are more likely to develop subnational criminal governance regimes where central authorities have left local authorities politically unprotected.…”
Section: Criminal Governance and Societal Resistance: Theoretical Guimentioning
confidence: 99%
“…Its aim is generally to provoke their removal or render them less effective in pursuing agendas that the group dislikes (Dal Bó, Dal Bó, and Di Tella 2003). Country factors may facilitate such violence; for example, in Mexico the number of narco-assassinations has increased since 2005 as a result of growing criminal fragmentation and political pluralization (Blume 2017).…”
Section: Violence Against Politiciansmentioning
confidence: 99%